Everything in its right place: resident memory CD8+ T cell immunosurveillance of HIV infection. Issue 2 (March 2019) - Buggert, Marcus; Japp, Alberto Sada; Betts, Michael R.
Abstract : Purpose of review: To introduce emerging concepts in tissue resident CD8 + T cell immunosurveillance and their relevance to control HIV infection. Recent findings: It is well appreciated that HIV preferentially infects and persists in CD4 + T cells located in gut and in lymphoid tissue, yet the majority of known immunological correlates of HIV control are derived from peripheral blood. Instead, tissue-based immunological surveillance likely dictates the course of infection. Recent studies have established that nonrecirculating resident memory CD4 + and CD8 + T cells can be found in virtually every human tissue. These cells bear a transcriptional profile of tissue retention and immediate effector function, suggesting a pivotal role in protective immunity. Resident memory CD8 + T cells specific for HIV have been found in higher numbers in sites of HIV persistence (gut and lymph nodes), and are inversely associated with HIV viral titers. These findings, along with previous studies on tissue-derived cells now known to include resident memory cells, shed new light on the compartmentalization of the immune response against HIV and its correlates of protection. Summary: Resident memory CD8 + T cells represent a critical unexplored component of immune surveillance in the setting of HIV infection. Understanding the induction, dynamics, and functional properties of HIV-specific resident memory T cells in relevant tissues will better inform efforts in the treatment, control, and potential cure of HIV infection.